Cambodia's postgraduate students: Emerging patterns and trends. - Walker, Karen (Penerbit Universiti Kebangsaan Malaysia, 2012)
A study was conducted to fill gaps in the description of the features of Cambodia’s postgraduate student population. Using an online survey of a master’s programme at a Cambodian government university, the profile that emerged showed that most postgraduate students were male, married, and urban. Postgraduate students reported investing up to a third of their annual income on study and study-related costs, and little use was made of institutional resources like libraries, computers, and the Internet. A strong belief was held amongst respondents that attainment of a postgraduate qualification would be materially beneficial for their career prospects. It was widely believed that universities needed to establish clear links between the programmes of study they offered and the future skilled labour needs of the country.